2020
DOI: 10.3390/jcm9020359
|View full text |Cite
|
Sign up to set email alerts
|

Central Resistance to Thyroid Hormones in Morbidly Obese Subjects Is Reversed after Bariatric Surgery-Induced Weight Loss

Abstract: Endocrine abnormalities are common in obesity, including altered thyroid function. The altered thyroid function of obesity may be due to a mild acquired resistance to the thyroid hormone. The aim of this study was to investigate the effect of weight loss after bariatric surgery (BS) on resistance to thyroid hormones in patients with extreme obesity compared with a control group. We performed an observational study evaluating patients with extreme obesity who underwent BS. We included 106 patients (83 women) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 48 publications
(78 reference statements)
2
29
1
Order By: Relevance
“…In our previous study we observed that TSH levels decreased in correlation with insulin resistance following bariatric surgery [6]. Juiz-Valiña et al [7] also reported similar findings. We therefore think that L-T4 requirements decreased through a similar pathway to the decrease in insulin resistance occurring with weight loss in association with thyroid hormone resistance in obese patients.…”
Section: Discussionsupporting
confidence: 67%
“…In our previous study we observed that TSH levels decreased in correlation with insulin resistance following bariatric surgery [6]. Juiz-Valiña et al [7] also reported similar findings. We therefore think that L-T4 requirements decreased through a similar pathway to the decrease in insulin resistance occurring with weight loss in association with thyroid hormone resistance in obese patients.…”
Section: Discussionsupporting
confidence: 67%
“…first proposed the calculation of TSHI for estimating the sensitivity of pituitary to thyroid hormones ( 20 ). Impaired HPT sensitivity to thyroid hormones has been suggested to be related to multiple unfavorable clinical outcomes, including obesity ( 21 ), T2DM ( 10 , 22 ), and decreased estimated glomerular filtration rate (eGFR) ( 22 ). In 2019, Laclaustra et al.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment with GH in a large group of adult GH-deficient patients has been found to induce a significant reduction in FT4 [ 47 ]. The increased TSH and central resistance to thyroid hormones of obesity [ 7 , 8 ] could be a contributory factor to the altered GH–IGF-1 axis. A positive synchronous serum concentration correlation between TSH and GH assessed from 24-h hormone concentrations measured at 10-min intervals has been found in healthy older subjects [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…This sample size allows the estimation of change in GH and IGF-1 values after bariatric surgery with a 95% confidence and a precision of ±0.6 µg/L and ±20.5 µg/L, respectively. For this sample size estimation, standard deviation values obtained from a previous study was used [ 8 ]. The inclusion criteria for bariatric surgery were to be between 18 and 65 years old, have a BMI > 40 kg/m 2 (or >35 kg/m 2 and at least one serious obesity-related health problem, such as diabetes, high blood pressure or sleep apnea), failure of previous nonsurgical attempts at weight reduction, expectation that patient will adhere to postoperative care and follow-up visits with team members.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation